Protein and lipid oxidation in guinea pig brain during acute high altitude exposure (4540 m) - Cárdenas, Anthony M. (2012)
The aim of this study was to assess the effect of high altitude exposure time on the oxidation of proteins and lipids from guinea pig brain tissue. Fifty guinea pigs (sea level natives) were taken up to Morococha (4540 m) and sacrificed on days 1, 3, 7 and 14, after arrival. Phospholipase A2 (PLA2) activity, levels of lipid hydroperoxides (LOOH) and malondialdehyde (TBARS) were determined as markers of lipid oxidation. Carbonyl groups (CG) were also determined as markers of protein oxidation. Activities of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) were also determined. PLA2 activity increased until third day. LOOH, TBARS and CG levels were found to be increased the first day; LOOH levels showed a declining trend but TBARS levels remained high, CG concentration decreased below the control group levels on the third day. The activities of antioxidant enzymes GPx and CAT increased from the first day; SOD activity increased until the third day and declined afterwards. It can be concluded that exposure to high altitude directly influences the oxidation of lipids and proteins. The decrease in CG levels might be due to proteolytic system activation, which would degrade the proteins damaged by Reactive Oxygen Species (ROS). The altitude exposure also influences the activity of antioxidant enzymes, especially GPx, which plays an important role in the detoxification of LOOH.